Symptoms and signs of lower gastrointestinal disease. (March 2015) - Coda, Sergio; Thillainayagam, Andrew V.
Abstract Symptoms of lower gastrointestinal (GI) disease are common and frequently trigger consultation in primary and secondary care. Diarrhoea, abdominal pain and constipation are presentations of a wide range of different underlying pathologies, from chronic, benign, functional conditions to acutely life-threatening emergencies. Lower GI bleeding is often due to serious pathology and requires rational investigation based on a systematic clinical assessment. Extra-intestinal manifestations of lower GI disease can often give a clue to the underlying diagnosis. In this contribution, we review the aetiology, clinical features, investigations and management for a range of lower GI symptoms, namely diarrhoea, constipation, lower GI bleeding, bloating and abdominal pain.